EFEKTIVITAS PENGGUNAAN GANYONG (Canna Edulis) SEBAGAI MAKANAN ALTERNATIF DIET BAGI PENDERITA DIABETES - Abdul Hamid; Rafi'ah Rafi'ah; Iga Maliga (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Diabetes mellitus (DM) has become a world health problem and continues, especially in developing countries and is a health problem that impacts human resources. The number of cases and the prevalence of diabetes have continued to increase over the last few decades. Sumbawa Regency is one of the areas in NTB where DM sufferers are increasing. The purpose of this study was to see its effectiveness as food for people with type 2 diabetes. This experimental research was an experiment. Diabetes Mellitus patients received direct treatment by offering Ganyong as food as food for the rice group. The research was conducted in 3 health centers located in the working area of Sumbawa Regency. This research involved 40 respondents in which 20 respondents became the Experiment group and 20 respondents became the Control group. Data were collected through interviews and observations using questionnaires and blood samples were examined for respondents to see their initial blood sugar levels before being given treatment to the experimental group. Based on the results of the t test analysis on Diabetes Mellitus Patients, there is a significant difference between treatment and after treatment with a difference value of 72.25 and a value of 0.040. While the results of laboratory analysis using the luff-schroll test with the titration method found that the carbohydrate content in ganyong was 84.7%, the glucose content was 23%, the air content was 12.1% and the ash content was 3.86%.